Cancer research communications - American Association for Cancer Research (American Association for Cancer Research, 2021)
Scope inculdes: Molecular and Cellular Biology -- Tumor Biology -- Immuno-oncology -- Therapeutic Research and Development -- Emerging Technologies and Data Science -- Precision Medicine and Biomarkers -- Clinical Research and Trials -- Epidemiology and Prevention -- Health Policy and Outcomes Research.
Keywords: Cancer : Periodicals; Cancer : Treatment : Periodicals; Oncology; Neoplasms; Medical Oncology; Cancer : Périodiques; Cancer : Traitement : Périodiques; Cancérologie; Cancer : Research; Cancer : Treatment